The role of knowledge processes in enhancing the capacity of internal auditors - Zuhair KHudhair Abbas, Marwan Amer Nsaif, (Opción, 2019)
The aim of the study was to identify the role of knowledge processes (knowledge diagnosis, knowledge generation, knowledge storage, knowledge implementation, knowledge assessment) in Iraqi public universities and their relation to internal auditors’ abilities. The sample consisted of (50) internal auditors, the researchers used the analytical descriptive approach in data analysis and testing of hypotheses. As a result, Iraqi government universities use knowledge processes at an average level of assessment. In conclusion, there is a strong positive relationship between knowledge processes and internal auditor capabilities